Falls in ambulatory non-demented patients with Parkinson's disease - Rascol, Olivier (2015)
<abstracttext />This study aimed at determining the prevalence of falling in PD patients, to assess generic and disease-specific clinical and pharmacological factors, relationship with health-related quality of life (HR-QoL) and changes in falls from OFF to ON in patients with motor fluctuations. Six-hundred and eighty-three PD patients of the COPARK survey were evaluated (11 had missing data and were excluded from the analysis). Patients with falls were identified as those with a UPDRS Item 13 ¡Ý 1 in the ON condition. All patients were assessed in a standardized manner [demographics, treatments, Unified PD Rating Scale (UPDRS), Hospital Anxiety and Depression Scale, Pittsburg questionnaire and HR-QoL scales (SF36, PDQ39)]. Falling was reported by 108/672 (16 %) PD patients during the ON state and prevalence increased according to PD severity, from 5 % in Hoehn and Yahr stage 1-60 % in stage 4. Falling was significantly related to lower HR-QoL. Falling correlated with (1) generic factors such as female gender, age at the end of academic studies and diuretics consumption, (2) motor PD-specific factors including disease severity, frozen gait, difficulties when arising from a chair, dyskinesia and higher levodopa daily equivalent dose and (3) non-motor PD-specific factors such as orthostatic hypotension and hallucinations. Falling was more frequent in OFF than in ON in 48/74 (64 %) patients with motor fluctuations and remained unchanged in 27 patients (36 %). In summary, falling affected a significant proportion of PD patients, especially in advanced stages. It was associated with a variety of generic and PD-specific factors and was related to reduced HR-QoL.</abstracttext />